Peripheral Blood T-lymphocyte Phenotypes in Mother-Child Pairs Stratified by the Maternal HPV Status: Persistent HPV16 vs. HPV-Negative: A Case-Control Study - Suominen Helmi; Paaso Anna; Koskimaa Hanna-Mari; Grénman Seija; Syrjänen Kari; Syrjänen Stina; Louvanto Karoliina (MDPI, 2025)
Only few studies exist on the phenotype distribution of peripheral blood lymphocytes concerning persistent oral HPV infection. T-lymphocyte subsets were phenotyped in women who had persistent genital or oral HPV16 infection, using HPV-negative women as a reference group. A subset of 42 mothers and their children (n = 28), were stratified into two groups according to the mothers' HPV status. PBMCs from previously cryopreserved venous samples were immunophenotyped by flow cytometry. Proportions of the CD4+ or CD8+ lymphocytes by their immunophenotype subsets were compared between HPV-positive and -negative mothers and their children. The mean rank distribution of CD8+ memory cells was significantly higher among mothers with persistent genital HPV16 infection. The median levels of both the antigen-presenting CD4+ cells and activated CD8+ cells were significantly lower in mothers with persistent oral HPV16 infection. When oral and genital HPV16-persistors were analyzed as a group, a marker of terminal effector cells was significantly increased as compared to HPV-negative women. Significantly higher levels of activated CD4+, CD8+ and circulating CD8+ memory cells were found among children whose mothers had persistent oral HPV16 infection. Persistent HPV16 infections are associated with changes in peripheral blood T-lymphocyte subsets. The mother's persistent oral HPV16 infection possibly results in immune alterations in her offspring.